2021
DOI: 10.3892/ijo.2021.5226
|View full text |Cite
|
Sign up to set email alerts
|

Current research status of TNFAIP8 in tumours and other inflammatory conditions (Review)

Abstract: Tumour necrosis factor (TNF)-α-inducible protein 8 (TNFAIP8) is the founding member of the TIPE family. According to accumulating evidence, TNFAIP8 plays a pivotal role in the regulation of a variety of tumours, as well as inflammatory diseases. TNFAIP8 is suggested to act as an anti-apoptotic protein, affecting proliferation, metastasis, invasion, angiogenesis, drug resistance and immune response through multiple signalling pathways. From the clinical point of view, further studies should be required to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…Our findings are consistent with previous studies that have identified SOWAHD and TNFAIP8 as potential prognostic biomarkers in several different types of cancer 31,32 . For example, SOWAHD was found to be significantly downregulated in hepatocellular carcinoma, and its overexpression inhibited the proliferation and invasion of hepatocellular carcinoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with previous studies that have identified SOWAHD and TNFAIP8 as potential prognostic biomarkers in several different types of cancer 31,32 . For example, SOWAHD was found to be significantly downregulated in hepatocellular carcinoma, and its overexpression inhibited the proliferation and invasion of hepatocellular carcinoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…TNFAIP8 promoted GBM migration, invasion and proliferation, implying a transition towards MES subtype. Moreover, other researches have illustrated that TNFAIP8 exerts pro-angiogenic, anti-radiotherapy and immune suppressive effects in tumors (11,27). Considering that malignant behavior such as resistance to therapy, angiogenesis, increased motility and viability or recruitment of immune suppressive cells were hallmarks for MES GBM (31,32), it is reasonable to propose that TNFAIP8 exerted oncogenic effects through induction of MES phenotype in GBM.…”
Section: Discussionmentioning
confidence: 98%
“…TNFAIP8 plays a pivotal role in regulation of a variety of tumors and in ammatory diseases (27). Kumar et al rst identi ed a partial cDNA clone for TNFAIP8 which ampli ed in a metastatic and radioresistant head and neck squamous cell carcinoma (HNSCC)-derived cell line(8), endorsing its importance in cell survival, tumor growth and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Target gene prediction and Dual-Luciferase reporter assay miR-24-1-5p's potential molecular targets were predicted using the miRDB database (https://mirdb.org/). Among the potential targets, we speci cally focused on TNFAIP8, which is an integral component of the TNFAIP8/NF-κB/TNF-α pathway known for its signi cant involvement in in ammatory diseases [13]. A conventional method was used to construct wild-type (WT)-TNFAIP8 plasmids fused with luciferase genes and mutant (MUT) TNFAIP8 fusion genes.…”
Section: Thp-1 Treatment With Pd-exosmentioning
confidence: 99%